PERENCANAAN JARINGAN IRIGASI POMPA DI DESA MUARA EMIL KECAMATAN TANJUNG AGUNG KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Olviani, Jeni; Pudjowati, Utami Retno; Hanggara, Ikrar (Prokons: Jurnal Teknik Sipil, 2024)
Muara Emil Village is one of the villages known as a rice-producing village in Muara Enim Regency. The problem is the river that is the source of water in the village is located at a lower elevation than the agricultural land that requires water flow. For this reason, a pump irrigation network was applicated to facilitate the flow of water to rice plants. The purpose of this thesis is to determine the availability of water available at the water intake source, to determine the water requirements needed by plants, to determine the capacity of the pump that must be used, to determine the capacity and dimensions of the irrigation channel, to determine the capacity of the reservoir and to estimate the cost of building a pump irrigation network. The data required are interview data, river water level data, rainfall data at the 3 nearest stations, climatology data, and unit prices for Muara Enim Regency work in 2023. The method for processing reliable rainfall is the basic year method, channel dimensions use the manning formula. The planning results are as follows: the highest water availability is 935 m3/second. The water requirement needed by plants is 0.00235 m3/second. The pump capacity used is 459.8m3/hour. The reservoir capacity is 20.915m3/hour with dimensions of 70 x 100 x 3.5m. The cost required to create a pump irrigation network is Rp 9.672.363.478